Evaluation of a novel urinary antigen test kit for diagnosing Legionella pneumonia. (February 2021) - Ito, Akihiro; Yamamoto, Yoshihiro; Ishii, Yoshikazu; Okazaki, Akihito; Ishiura, Yoshihisa; Kawagishi, Yukio; Takiguchi, Yasuo; Kishi, Kazuma; Taguchi, Yoshio; Shinzato, Takashi; Okochi, Yasumi; Hayashi, Ryuji; et al.
Highlights: A novel urinary antigen test kit was found to be useful for diagnosing Legionella pneumonia. The novel kit had a good diagnostic correlation with existing kits. Only the novel kit was able to diagnose non- Legionella pneumophila serogroup 1 pneumonia. Abstract: Objectives: The aim of this study was to evaluate the diagnostic utility of a novel test kit that could theoretically detect all serogroups of Legionella pneumophila for diagnosing Legionella pneumonia, in comparison with existing kits. Methods: This study was conducted in 16 hospitals in Japan from April 2016 to December 2018. Three urinary antigen test kits were used: the novel kit (LAC-116), BinaxNOW Legionella (Binax), and Q-line Kyokutou Legionella (Q-line). In addition, sputum culture and nucleic acid detection tests and serum antibody tests were performed where possible. The diagnostic accuracy and correlations of the novel kit with the two existing kits were analyzed. Results: In total, 56 patients were diagnosed with Legionella pneumonia. The sensitivities of LAC-116, Binax, and Q-line were 79%, 84%, and 71%, respectively. The overall match rate between LAC-116 and Binax was 96.8% and between LAC-116 and Q-line was 96.4%. One patient had L. pneumophila serogroup 2, and only LAC-116 showed a positive result, whereas Binax and Q-line did not. Conclusions: The novel Legionella urinary antigen test kit was useful for diagnosing Legionella pneumonia. In addition, it could detect Legionella pneumonia caused by non- L. pneumophila serogroup 1.